The impact of the Raymond Ackerman Academy of entrepreneurial development (RAA) in creating improved and sustainable livelihoods amongst academy graduates. - Yiannakaris, Elli Cherissa (School of Economics, 2020)
In response to a youth unemployment crisis, the South African government has placed a strong emphasis on entrepreneurship and entrepreneurship education (EE) as a strategy for job creation. Using the Raymond Ackerman Academy of Entrepreneurial Development (RAA) as a case study, this dissertation seeks to investigate the impact of EE for youth considered vulnerable to unemployment. It specifically examines whether EE has been a mechanism to support black, urban township youth, based on the Cape Flats, to overcome their structural circumstances to put them on a path towards improved livelihoods. Then if so, how. Its key research questions are, What has been the nature of the impact of the RAA Cape Town on graduates’ personal development and economic livelihoods? Then, if the RAA has impacted the personal development and economic livelihoods of participants in the programme, how has it done so? The study, which drew predominantly on qualitative research combined with quantitative surveys and methods, showed that participating in the RAA entrepreneurship programme impacted participants both personally and economically. Participants found a combination of programme factors valuable, including the person-centred approach, the combination of the business and personal development curriculum, the role of staff, and access to networks and opportunities. The RAA seemed to build confidence, developed an entrepreneurial mindset and served as a launch pad towards improved economic livelihoods, albeit not exclusively through starting a business. The study was unable to ascertain whether outcomes were entirely attributed to the EE programme run by the RAA. Analysis of the counterfactual group showed that these youth were able to move forward without participating in the RAA, but not to the degree of participants in the programme. The counterfactual data also gave valuable insight into how for some participants emotional stress and financial responsibility contributed to their withdrawal from the programme, and that without additional support may prevent some young people from getting ahead. The study builds on the EE literature that proposes that design of EE should be holistic, multi-dimensional, and experiential; and should carefully consider a broad spectrum of elements from course content, to staff, to the context and environment in which it is presented. It indicated that EE that teaches “through” entrepreneurship versus “for” entrepreneurship does appear to impact young people’s ability to engage in the economy (mostly through employment) and can increase their earning potential. The study supports the argument that EE can launch youth towards improved economic livelihoods; and can therefore serve as an impactful strategy for alleviating youth unemployment.